Déborah González / Helena Bermúdez Sabel (Eds.): Digital Humanities: Looks towards the Middle Ages. Berlin / Boston: De Gruyter, 2019, 259 pp. ISBN: 978-3-11-058541-4. - Kawasaki, Yoshifumi (Philologia Hispalensis, 2021)
Review of the work of Déborah González / Helena Bermúdez Sabel (Eds.): Digital Humanities: Looks towards the Middle Ages. Berlin / Boston: De Gruyter, 2019.